2019
DOI: 10.2134/jeq2018.04.0129
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vegetated Buffer Strips in Controlling Legacy Phosphorus Exports from Agricultural Land

Abstract: The continued phosphorus (P) impairment of freshwaters and the associated risk of eutrophication raise questions regarding the efficiency of current beneficial management practices (BMPs) for improving water quality. Vegetated buffer strips (VBSs) are widely encouraged BMPs for reducing P export from agricultural land. However, there is a lack of evidence regarding the longterm efficiency of VBSs for reducing legacy P losses. This research used soil analyses to investigate the P removal efficiency of an unmana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…3a), which suggests contribution of P from adjacent farmland. An increase in TP and labile Pi of buffer strip soil compared with adjoining cropland was previously described by Habibiandehkordi et al (2019) and Roberts et al (2012). Furthermore, DPS values were highest in buffer strip soil (reaching up to 27%; Supplemental Table S3).…”
Section: Comparison Of Transitional Ecotonessupporting
confidence: 68%
“…3a), which suggests contribution of P from adjacent farmland. An increase in TP and labile Pi of buffer strip soil compared with adjoining cropland was previously described by Habibiandehkordi et al (2019) and Roberts et al (2012). Furthermore, DPS values were highest in buffer strip soil (reaching up to 27%; Supplemental Table S3).…”
Section: Comparison Of Transitional Ecotonessupporting
confidence: 68%
“…The plants also play an important role in intercepting agricultural non-point source pollutants. The interception efficiency of pollutants depends mainly on the vegetation type [37]. The reason why the sweet clover had high nitrogen retention efficiency was because it was a legume, which has good nitrogen fixation ability.…”
Section: Discussionmentioning
confidence: 99%
“…The longer‐term functioning of VBSs for storage of sediment and P has been questioned in the international literature, with the concern being that buffers may become a future P source due to decreasing soil P sorption capacities with age and P loading (Hoffmann et al, 2009; Stutter et al, 2009). In their study of a 57‐yr‐old unmanaged VBS, Habibiandehkordi et al (2019) found significantly higher mean masses of sediment and P in surface soils at the border of the VBS (6966 kg total P ha −1 and 10702 Mg sediment ha −1 ) than either 5 m upslope into the field (3956 kg total P ha −1 and 5346 Mg sediment ha −1 ) or 5 m into the VBS (2776 kg total P ha −1 and 3992 Mg sediment ha −1 ). They also found that surface soils at 5 m into the VBS had a significantly greater P sorption capacity and a smaller degree of P saturation than adjacent field soils, the latter attributed to P enrichment in the field resulting from manure or fertilizer application.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
“…Hille et al (2019) quantified the effects of annual vegetation harvesting to deplete the accumulated pools of soil P as P‐enriched fines were trapped over years in the buffer. Habibiandehkordi et al (2019) observed that the P saturation of VBS topsoil as compared with subsoil had increased as little as ∼11% over the 57‐yr period, and the authors concluded that their sites did not support the hypothesis of saturation of VBS topsoils with P. It would be advantageous to bring in knowledge of P sorption and saturation in different soil types that is well developed in the agronomic literature to support recommendations for reducing P in differing buffer soil matrices.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 1 more Smart Citation